Keefektifan Penggunaan Model Pembelajaran Kooperatif tipe STAD pada Materi Perkembangan Teknologi di Universitas Cokroaminoto Palopo - Yuni Fayanti Sukri (Cokroaminoto Journal of Primary Education, 2018)
This study uses a quantitative approach with Randomized Control Group Design experimental method. The experimental class was treated using the GI model, the control class used the STAD model with the material of technological development. Sample This study used 2 experimental classes involving 40 students and 2 control classes involving 40 students taken from 91 selected by purposive random sampling. Research instruments, affective and psychomotor observation sheets, response questionnaires and cognitive test pre-test and post-test results. Data analysis uses the two-way Anava Test. The results of the analysis of the social studies learning process on the technological developments taught by the GI type cooperative learning model encourage students to be more creative and critical. Students are more focused and directly involved in determining the topics they like to investigate. Effectiveness test results show classical learning completeness above 75%. The value of cognitive improvement in student learning is the gain value of the four groups at 0.3 ≤ g <0.7. Suggestions that can be given, the lecturer must pay more attention to the type because it can affect student learning outcomes.